Electroacupuncture for relieving itching in atopic eczema: study protocol for a multicenter, randomized, sham-controlled trial - Wang, Si-han; Liang, Rui-long; Yang, Han; Cai, Xiao-ce; Wang, Jiao; Sun, Xiao-ying; Chen, Jia-le; Wang, Chun-xiao; Jiang, Wen-cheng; Li, Xin (Frontiers in Medicine, 2023)
Background Atopic eczema (AE) is a common atopic inflammatory skin disease affecting 2.1–4.9% of the population in different countries. Pruritus, one of the most burdensome symptoms, is often underestimated for the problems it can cause, creating a vicious loop of itching, scratching, and lichenification. Therefore, further research into practical and safe treatments that relieve itchy symptoms and enhance skin protection is key to overcoming AE. Acupuncture, with or without electrical stimulation, is one of the most commonly used therapeutic measures to treat AE. This trial aimed to objectively evaluate the efficacy and safety of the electroacupuncture (EA) antipruritic technique in AE pruritus and obtain high-level clinical evidence for the popularization and application of EA for AE. Methods and analysis This multicenter, single-blinded, randomized controlled trial is planned to transpire from April 15, 2023, to June 30, 2025. We will recruit 132 participants with AE (44 per group). Participants will be assigned randomly to three equal-sized groups: EA, sham electroacupuncture, and sham acupuncture. Treatment will be administered three times a week during the 2-week intervention phase. The primary outcome measure is the Visual Analog Scale, with a numeric rating scale to evaluate pruritus. Secondary outcome measures include the Eczema Area and Severity Index and Dermatology Life Quality Index. Other outcome measures include physical examination, serum IgE, and safety evaluation. The number, nature, and severity of adverse events will be carefully recorded. Trial registration ClinicalTrials.gov, 22Y11922200. Registered 3 September 2022, https://register.clinicaltrials.gov.